pengetahuan sex education pada siswa/i kelas XI di SMA Negeri 1 Kampar Timur - Lora marlita; Nofri Naldi (Jurnal Ilmu Kesehatan Abdurrab, 2023)
ABSTRACT At this time sexual education is very important for society, especially among adolescents because this aims to create a healthy emotional attitude towards sexual problems and guide adolescents towards healthy living and being responsible for their sexual life. This study aims to find out the description of sex education knowledge in class XI students at SMA Negeri 1 Kampar Timur in 2023. This research method is a quantitative study with a descriptive design. The total population in this study was 330 with sampling using the cluster sampling technique so that the number of samples used was 183 people with the instrument using a multiple choice question questionnaire consisting of 15 questions which were distributed by coming to classes at SMA Negeri 1 Kampar Timur . The results of this study showed that 64 students (35.0%) had satisfactory knowledge, 80 students (43.7%) had satisfiable knowledge, and 39 people (21.3%) had excellent knowledge. The level of knowledge of Class XI students at SMA Negeri 1 Kampar Timur about Sex Education is that 80 people (43.7%) have sufficient knowledge. It is hoped that all related parties will help increase the knowledge of students who have weak or insufficient knowledge of sex educati